UAV strike threat protection system using neural network analysis units - Перепеліцин, Сергій Олександрович (Science-based technologies, 2020)
Unmanned aerial vehicles (UAVs), which have proved their ability to conduct aerial reconnaissance much more effectively than manned aircraft and perform other combat support tasks by striking at the enemy, became one of the means of new weapons in military conflicts of the late 20th and early 21st centuries. Today it is impossible to imagine an army without an UAV, because they point to the target, bring artillery, adjust fire, transmit intelligence directly to the headquarters, and most importantly, save the lives of fighters. This paper presents an analysis of the use of UAVs for photo and video shooting in the interests of intelligence, which as a result gives large arrays of images in real time. The system of pattern recognition on the ground, recognition of speech information, quick mapping of the area before Bonwit operations, face recognition in the interests of identification, recognition of radio signals under conditions of adversary’s use of active interference - this is not a complete list of tasks by which they can find application of the properties of neural networks and neural network analysis. Unmanned reconnaissance aircraft together with manned and space reconnaissance form the reconnaissance triad. Military experts from developed countries of the world believe that in a modern combat situation, reconnaissance UAVs can more effectively and efficiently, in comparison with reconnaissance pilots, solve airborne reconnaissance missions. This reduces the time to bring the received intelligence information to the appropriate governing body. The success of using an UAV depends not only on the quality of the devices themselves, but also on the training of pilots, the model of combat use used, compliance with operating conditions, routine maintenance of the resource, that is, the availability of service support and a repair base, as well as the necessary conditions for storage and mobility UAV crew when moving along the front. The analysis allows us to conclude that the role of reconnaissance unmanned aircraft in the aerial reconnaissance system for operational support in reconnaissance is growing.